Geophysical reconnaissance of karst sinkhole occurrences in Jeram, Kinta Valley, West Malaysia after the 2004 Indian Ocean earthquake - Muhammad, R.F.; Al-kouri, O.; Yassin, R.; Lat, C.N. (2011)
Geophysical and geospatial reconnaissance of karst features associated with sinkholes has been carried out in Jeram, Perak, West Malaysia. A rapid increase of sinkholes occurrences were reported after the disastrous 26th Dec. 2004 earthquake in Sumatera. Over 45 sinkholes of various sizes occurred in a small area of the ex-mine land. Many cavities are present in the subsurface karst that is covered by thin layers of loose sands and clay materials. These cavities are thought to be pre-existing features that had been rapidly filled with sand/clay, due to the tremor triggered from the earthquake.